Ecology and allometry predict the evolution of avian developmental durations - Christopher R. Cooney (Nature Portfolio, 2020)
Developmental duration is a key life-history trait. Cooney et al. compile data on 3096 bird species to quantify the degree to which phylogenetic history, body size and ecological variables like predation risk or breeding phenology influence variation in developmental duration.